Chapter 7: Marine environment and sustainable development governance - Varjopuro, Riku (Edward Elgar Publishing, 2022)
Achieving sustainability in an emerging economy characterized by increasing inequalities is challenging. Within this framework economic growth, poverty reduction and environmental sustainability are often viewed as trade-offs. Simultaneously addressing these objectives is difficult. This chapter examines the "Sembrando Vida" (Sowing Life) anti-poverty program in Mexico which aims to link rural poverty reduction to environmentally sustainable practices through a widespread tree planting subsidized by the government. The chapter utilizes policy coherence for development (PCD) as a methodology to highlight specific mechanisms which need to be addressed to make the program more effective and sustainable. It responds to the question: "How can emerging states, such as Mexico, address poverty while simultaneously promoting sustainability?"